Refractive errors of medical students in Turkey: One year follow-up of refraction and biometry - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Purpose. This study was conducted to determine the prevalence of refractive errors in Turkish medical students as well as to determine the change in refractive status of medical students within 1 year. Besides general refractive characteristics of the students, the possible relationship between the occurrence of myopia and several factors was also determined. Methods. Two hundred and seven medical students (114 female/93 male) were checked for their refractive status as determined by cycloplegic autorefraction. In addition to keratometric and biometric measurements students also answered a detailed questionnaire. One year later, medical students who participated to the study were re-examined. Results. Myopia occurred in 32.9% of medical students with low myopia (spherical equivalent between -0.75 diopters [D] and -2.99 D) being the most common type (81%). The frequency of myopia was not significantly different between female and male medical students (37.7 and 26.8%, respectively; p = 0.13). Adult onset myopia (onset at age 18 years or older) comprised 14.7% of all myopia cases. Myopic students were significantly more likely to report parental myopia. The percentage of myopes and nonmyopes reporting having one or two myopic parents was 51.5 and 28.8%, respectively (p = 0.002). Parental myopia was also an independent risk factor associated with the occurrence of myopia on multivariate analysis (odds ratio [OR] = 3.69, 95% confidence interval [CI] = 1.98-6.87). Nonmyopes also reported a significantly higher prevalence of outdoor activity before and at age seven (68.4%) than did myopes (48.6%), (p = 0.009). Outdoor activity during early childhood was found to be protective for myopia on multivariate analysis (OR = 0.44, %95 CI = 0.23-0.82). There was no significant difference between myopes and nonmyopes with respect to amount of close-up activity. No significant shift of refraction occurred within 1 year. Conclusions. About one-third of Turkish medical students had myopia. Parental myopia was more common among myopic students and was a risk factor for the occurrence of myopia suggesting a familial predisposition. Outdoor activity in early childhood has had a protective role against the development of myopia in this study sample.
Keywords: refractive error; myopia; medical student; HIGH MYOPIA MAPS; ONSET MYOPIA; RISK-FACTORS; SINGAPORE; CHILDREN; LOCUS; WORK; ACHIEVEMENT; PREVALENCE; NEARWORK